2012
DOI: 10.4236/ijoc.2012.21008
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of <i>cis</i>-Substituted-3’-anilino-2’, 3’-dihydro-4-2’-benzo[<i>b</i>]furanylcoumarins via Intramolecular Aldol Reactions

Abstract: The present study reports the reaction of 4-bromomethylcoumarins with salicylidineaniline in acetone with two equivalents of potassium carbonate resulted in the formation of title compounds at room temperature via intramolecular aldolization. The obtained compound is thermodynamically and kinetically stable with highly stereoselective and excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Present report illustrates a rare C—C bond forming reaction between the N ‐hydroxymethylated product and an enolate stabilized C 4− CH 2 function attached to the coumarin ring. Reactivity of the C‐4 methylene group of coumarin has been demonstrated by our earlier work related to the reactions of ortho substituted 4‐aryloxymethyl coumarins leading to the formation of 4‐2′ benzo[ b ]furanyl coumarins , 2,3‐dihydrobenzofuranols , and the corresponding arylamines . Proposed structures 6 for the products obtained are supported by spectral data.…”
Section: Resultssupporting
confidence: 53%
“…Present report illustrates a rare C—C bond forming reaction between the N ‐hydroxymethylated product and an enolate stabilized C 4− CH 2 function attached to the coumarin ring. Reactivity of the C‐4 methylene group of coumarin has been demonstrated by our earlier work related to the reactions of ortho substituted 4‐aryloxymethyl coumarins leading to the formation of 4‐2′ benzo[ b ]furanyl coumarins , 2,3‐dihydrobenzofuranols , and the corresponding arylamines . Proposed structures 6 for the products obtained are supported by spectral data.…”
Section: Resultssupporting
confidence: 53%
“…Our interest in the dihydrobenzofuran, pyrimidine and pyranopyrazole coumarins analogs were we discussed the antimicrobial activity and identified that coumarinopyrimidines are selective against S.aureus . Prompted by the above cited observation; we were encouraged to synthesis coumarinodihydrofurano derivatives by using multicomponent reaction (MCRs) approach.…”
Section: Introductionmentioning
confidence: 99%